Life cycle development and approach of management consulting projects - Lopes da Costa, R.; Pereira, L. F.; Dias, Á.; Gonçalves, R.; Vinhas da Silva, R.; Teixeira, N. (International Journal of Applied Systemic Studies, 2024)
Management consulting projects are nowadays important support for companies that face a very difficult context and the mandatory step to change their business model to adapt and survive. However, the subject of this emerging area is not well studied and there is a lack of scientific literature. This research aims to develop a detail model of steps and objectives that must be implicit in the development of a project in management consulting. The results of the empirical analysis in the form of semi-structured interviews and questionnaires applied to management consultants and SME managers in Portugal reveal that a project in management consulting should be developed in nine steps starting from the pre-proposal and finishing in the measurement of five stages of development, including identification, characterisation, formulation, implementation, and evaluation.